The new and the tradition in Riacho Doce: between belonging and ruin - Coelho, Elisa Domingues [UNESP] (Univ Estadual Oeste Parana-unioeste, 2019)
Riacho Doce, along with O Moleque Ricardo, Pureza, Agua-Mele e Euridice, composes a part of the work of Jose Lins do Rego that escapes the traditional readings of cycles, memory and regionalism. This novel, in particular, suffered an even greater attack from criticism, which read, in the protagonism of the foreigner, a failed attempt by the author to innovate and escape the label of memorialist. This article, based on the analysis of the novel, seeks to expose how Jose Lins do Rego, by bringing a foreign protagonist and dedicating the whole first part of the story to her childhood in Sweden, has indeed innovated, but to operate a complexification of the elements that unite his work and insert them into a long trajectory of belonging that unites national and foreign, tradition and new. Through this trajectory of the protagonist Edna, we see land as the organizing axis of the novel, from her deep crisis of non-belonging in youth to her perspective, facing the new, crossing the sea and invading full the known conflict between tradition and change, endowing it with a new look. Dedicating an attentive reading, as Mario de Andrade did, we can see how these elements construct a tangle of trajectories and perspectives in which earth, tradition, the new, the foreigner and the search to belong or not to belong come close together, come apart, and, eventually, confront each other.
Keywords: Brazilian literature; Modernism; Jose Lins do Rego